Hiša športa - inovativen pristop k povezovanju in promociji športa - Bon, Marta (Šport (Ljubljana), 2018)
The House of Sport, located in the centre of Ljubljana, was established in 2013 with the aim to innovatively market and promote sport. On the one hand, this special place is designed to connect sport lovers, sport tourists and providers of (top) sports events, including the recreational ones, while on the other hand, it is about enforcing a notion that embodies sport promotion. The article is underpinned by a case study and action research which also encompassed own experience. We collected all the documentation of the first four years of operations. This is the first example of such a concept of sport promotion in Slovenia. Initially, the purpose of the House of Sport (founded by the Sport Ljubljana Public Institute) was to inform the inhabitants of and visitors to Ljubljana about sports events at the local, national and international levels. The bulk of activities encompass viewing of live matches in the company of sport legends and sport stars, sale of sports fan gear as well as socialising of fans from different clubs and different sports. The purpose of the catering offer is to increase the market share with the aim of self-financing of the House of Sport.
Keywords: druženje; Hiša športa; Ljubljana; promocija; šport; trženje